Yap1 safeguards mouse embryonic stem cells from excessive apoptosis during differentiation - Lucy LeBlanc; Bum-Kyu Lee; Andy C Yu; Mijeong Kim; Aparna V Kambhampati; Shannon M Dupont; Davide Seruggia; Byoung U Ryu; Stuart H Orkin; Jonghwan Kim (eLife, 2018)
Approximately, 30% of embryonic stem cells (ESCs) die after exiting self-renewal, but regulators of this process are not well known. Yap1 is a Hippo pathway transcriptional effector that plays numerous roles in development and cancer. However, its functions in ESC differentiation remain poorly characterized. We first reveal that ESCs lacking Yap1 experience massive cell death upon the exit from self-renewal. We subsequently show that Yap1 contextually protects differentiating, but not self-renewing, ESC from hyperactivation of the apoptotic cascade. Mechanistically, Yap1 strongly activates anti-apoptotic genes via cis-regulatory elements while mildly suppressing pro-apoptotic genes, which moderates the level of mitochondrial priming that occurs during differentiation. Individually modulating the expression of single apoptosis-related genes targeted by Yap1 is sufficient to augment or hinder survival during differentiation. Our demonstration of the context-dependent pro-survival functions of Yap1 during ESC differentiation contributes to our understanding of the balance between survival and death during cell fate changes.